A high-heat-value fast-burning heating powder and a preparation method thereof
Patent Information
- Application Number
- CN202610888386.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-18
- Publication Date
- 2026-10-20
AI Technical Summary
1)合金粉与氧化剂粒径匹配度差,导致局部燃烧不完全,残渣量通常高于8 wt%;
1、 燃烧性能优异:通过Al-Mg-B三元合金(B形成低熔点氧化物破坏氧化膜)、KClO4/CuO多孔复合氧化剂(CuO提供晶格氧,降低点火温度)与碳纳米管/石墨烯导热骨架(显著提高径向导热系数)的协同作用,配合氟橡胶的微爆效应,使得最小全燃烧时间≤38ms,质量燃烧热≥32 kJ·g-1,远优于对比专利 CN110890565B 常规 Fe / 高氯酸钾体系(燃烧热≤22.5 kJ/g,完全燃烧时间>75 ms)。
Smart Images

Figure FT_1 
Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of high energy density powder fuel technology, specifically to a fast-burning, high-calorific-value heating powder and its preparation method, which is mainly used as a heat source for thermal batteries, aerosol-free welding, or emergency heating bags. Background Technology
[0002] Products such as thermal batteries, aerosol-free welding, and emergency heating bags all require powder heat sources that can ignite rapidly in milliseconds, release heat concentratedly, and leave minimal residue. While traditional magnesium / aluminum-polytetrafluoroethylene (MTV) systems have relatively high burning rates, their heat of combustion is typically below 22 kJ·g. -1 While boron-based fuels have a high theoretical calorific value, their dense boron oxide layer on the surface hinders the contact between the fuel and the oxidant, resulting in long ignition delays and incomplete combustion.
[0003] Chinese patent application CN119069732A proposes a heating powder made by mechanically mixing Mg / Al binary alloy powder, Fe powder, and KClO4, which simultaneously improves the combustion rate and calorific value to a certain extent. However, this technology still has the following shortcomings: 1) Poor particle size matching between alloy powder and oxidant leads to incomplete local combustion, with residue typically exceeding 8 wt%; 2) The combustion products contain a large number of condensed particles, which can easily clog the gas passages of the thermal battery; 3) The system has low thermal conductivity, and the phenomenon of "external burning and internal scorching" occurs when the charge is slightly large.
[0004] Therefore, developing a heating powder that simultaneously meets the requirements of rapid combustion, high calorific value, low residue, and strong environmental adaptability has become an urgent technical challenge to be solved. Summary of the Invention
[0005] The purpose of this invention is to overcome the shortcomings of the prior art and provide a heating powder with fast combustion rate, high calorific value, low residue and strong environmental adaptability, as well as its preparation method.
[0006] Firstly, to achieve the above objectives, the present invention adopts the following technical solution: a fast-burning, high-calorific-value heating powder, comprising the following components by mass percentage: a) 35%~55% Al-Mg-B ternary alloy powder; b) 15%~25% Fe-Co composite powder; c) 20%~30% of a composite oxidant, wherein the composite oxidant is a complex of KClO4 and CuO; d) 3%~8% thermally conductive framework, which is composed of carbon nanotubes and graphene sheets; e) 0.5%~2% of fluororubber-based adhesive-pore-forming agent; The loose density of the heating powder is 1.25~1.45 g·cm³. -3 The minimum total combustion time under 25℃ and 1 atm air conditions is ≤38 ms, and the kinetic heat of combustion is ≥32 kJ·g. -1 The mass fraction of combustion residue is ≤5 wt%.
[0007] Preferably, as an improvement, the mass percentages of Al, Mg, and B in the Al-Mg-B ternary alloy powder are: Al 50%~70%, Mg 20%~35%, and B 5%~15%, respectively; the median particle size D50 of the alloy powder is 8~15 µm, and the maximum particle size is ≤45 µm.
[0008] Preferably, as an improvement, the Fe-Co composite powder has the following mass percentages: Fe 60%~80% and Co 20%~40%; the median particle size D50 of the Fe-Co composite powder is 12~20 µm.
[0009] Preferably, as an improvement, the composite oxidant is a porous particle obtained by antisolvent precipitation-freeze-drying of KClO4 and CuO in a mass ratio of 3:1 to 5:1, with a D50 of 20 to 35 µm and a specific surface area ≥ 2.5 m². 2 ·g -1 .
[0010] Preferably, as an improvement, the mass ratio of carbon nanotubes to graphene sheets in the thermally conductive framework is 1:2 to 2:1; the volume resistivity of the thermally conductive framework is ≤1×10⁻⁶. -3 Ω·cm.
[0011] Preferably, as an improvement, the fluororubber is a vinylidene fluoride-hexafluoropropylene copolymer with a Mooney viscosity ML(1+10) 121°C of 30~50; the fluororubber-based binder-pore-forming agent decomposes at 250~350°C to produce 0.3~0.8 mL·g. -1 Combustible gas.
[0012] Preferably, as an improvement, the surface of the Al-Mg-B ternary alloy powder has a self-limiting oxide shell with a thickness of 2~5 nm, which is formed by plasma passivation for 5~15 min at room temperature in an Ar mixed atmosphere containing 0.5~1 vol% O2.
[0013] Preferably, as an improvement, the Fe-Co composite powder is a flat, sheet-like particle obtained by high-energy ball milling, with a sheet thickness of 0.5~2 µm, a sheet diameter of 10~30 µm, and an aspect ratio of 5~15; and / or, the composite oxidant particles have through-pores with a pore size of 50~200 nm and a pore volume of 0.15~0.25 cm³. 3 ·g -1 .
[0014] Preferably, as an improvement, the thermally conductive skeleton is surface-modified with 3-aminopropyltriethoxysilane to achieve an interfacial shear strength ≥25 MPa with the fluororubber matrix.
[0015] Secondly, the present invention provides a method for preparing the above-mentioned fast-burning, high-calorific-value heating powder, comprising the following steps: S1. Alloy powder preparation: Al ingots, Mg ingots and B powder are induction melted in the target ratio and then atomized. The resulting powder is ball-milled to obtain Al-Mg-B ternary alloy powder with D50 of 8~15 µm. S2. Preparation of composite oxidant: KClO4 and CuO are dissolved in hot water in a certain proportion to form a saturated solution, which is then quickly poured into low-temperature ethanol for anti-solvent precipitation, and then freeze-dried to obtain a porous composite oxidant. S3, Triple Coupling Mixing: The thermally conductive framework is ultrasonically dispersed in an organic solvent to form a conductive paste. Then, a composite oxidant, Al-Mg-B ternary alloy powder, Fe-Co composite powder and fluororubber solution are added in sequence. Ultrasonic degassing is performed during stirring to obtain a uniform paste. S4. Spray granulation and drying: The paste is spray granulated and then subjected to gradient vacuum drying to obtain near-spherical particles; S5. Surface passivation treatment: The obtained particles are subjected to plasma treatment in an oxygen-containing inert atmosphere to obtain the fast-burning, high-calorific-value heating powder.
[0016] Preferably, as an improvement, the ball milling in step S1 is a differential step ball milling, with the following process parameters: using n-hexane as the process control agent, a ball-to-material ratio of 10:1, a rotation speed of 350 rpm, a 15-minute ball milling interval followed by a 5-minute pause, and a cumulative ball milling time of 90 minutes.
[0017] Preferably, as an improvement, step S3 specifically includes: ultrasonicating the thermally conductive skeleton in ethyl acetate for 10 min to form a conductive paste, then adding a composite oxidant and stirring at 200 rpm for 15 min; then adding Al-Mg-B ternary alloy powder and Fe-Co composite powder and mixing at 100 rpm for 10 min; finally adding an ethyl acetate solution of fluororubber, continuing to stir at 150 rpm for 20 min, and degassing in an ultrasonic field of 40 kHz and 200 W for 5 min.
[0018] Preferably, as an improvement, the parameters for spray granulation in step S4 are: a two-fluid nozzle is used, the atomization pressure is 0.3 MPa, the inlet air temperature is 110℃, and the outlet air temperature is 75℃; the parameters for gradient vacuum drying are: vacuum drying is performed sequentially at three temperature gradients of 25℃, 80℃, and 120℃ for a period of time, with a total drying time of 4 h.
[0019] Compared with the prior art, the present invention has the following beneficial effects: 1. Excellent combustion performance: Through the synergistic effect of Al-Mg-B ternary alloy (B forms low-melting-point oxides to destroy the oxide film), KClO4 / CuO porous composite oxidant (CuO provides lattice oxygen and reduces ignition temperature), and carbon nanotube / graphene thermally conductive framework (significantly improving radial thermal conductivity), combined with the micro-explosion effect of fluororubber, the minimum total combustion time is ≤38ms and the heat of combustion is ≥32 kJ·g-1, which is far superior to the conventional Fe / potassium perchlorate system in patent CN110890565B (heat of combustion ≤22.5 kJ / g, complete combustion time >75 ms).
[0020] 2. High combustion completeness and low residue: Through multi-scale particle size matching and three-dimensional heat conduction network, bulk synchronous combustion is achieved, and the mass fraction of combustion residue is ≤5 wt%; compared with the patented formula, the residue is generally 8%~12 wt%.
[0021] 3. Strong environmental adaptability: It can still be 100% ignited under extreme conditions of -40℃ and 5% relative humidity; the existing CN110890565B formula has an ignition failure rate of >12% under low temperature conditions.
[0022] 4. Excellent application performance: After being assembled into a thermal battery, the activation time is ≤80 ms, and the discharge capacity can be increased by more than 15%; compared with the corresponding patented thermal batteries, the activation time is generally ≥120 ms.
[0023] 5. Safe and environmentally friendly: There are no free heavy metals in the combustion products and the amount of chloride released is low. Attached Figure Description
[0024] Figure 1 This is a schematic diagram of the structure of the heating powder obtained in Example 1 of the present invention. Detailed Implementation
[0025] The following detailed description illustrates the specific implementation method: The technical solutions and effects of the present invention will be described in detail below with reference to specific embodiments and comparative examples. It should be understood that these embodiments are only for illustrating the present invention and are not intended to limit the scope of the present invention.
[0026] Example 1 This embodiment uses an optimally proportioned fast-burning, high-calorific-value heating powder, and the specific preparation steps are as follows: Preparation of S1 Al-Mg-B ternary alloy powder: Al ingots, Mg ingots, and B powder were induction melted at a mass ratio of Al 60%, Mg 25%, and B 15%, followed by gas atomization to form powder. The resulting powder was degassed in a vacuum environment at 200℃ for 2 hours to remove adsorbed water vapor and impurity gases. Subsequently, the powder was fed into a planetary ball mill, using n-hexane as the process control agent, with a ball-to-powder ratio of 10:1 and a rotation speed of 350 rpm for differential step ball milling. After each 15-minute ball milling, the mill was stopped and allowed to stand for 5 minutes, for a total of 90 minutes of ball milling, finally obtaining Al-Mg-B ternary alloy powder with a median particle size D50 of 12 µm.
[0027] S2. Preparation of the composite oxidant: KClO4 and CuO were mixed at a mass ratio of 4:1 and added to deionized water at 80℃, stirred until completely dissolved, to prepare a saturated salt solution. This saturated solution was then rapidly mixed with ethanol at 0℃ at a volume ratio of 1:3 for anti-solvent precipitation. The precipitate was collected and freeze-dried for 24 h to remove residual solvent, yielding a porous composite oxidant with a D50 of 28 µm and a specific surface area of 2.8 m². 2 ·g - ¹.
[0028] S3. Triple Coupling Mixture Preparation: A 1:1 mass ratio of carbon nanotubes and graphene sheets was selected as the thermally conductive framework. 5 wt% of the thermally conductive framework powder was added to ethyl acetate solvent and ultrasonically dispersed for 10 min to form a uniform conductive paste. 25 wt% of a self-made porous composite oxidant was added to the conductive paste and stirred at 200 rpm for 15 min to mix thoroughly. Then, 45 wt% of Al-Mg-B ternary alloy powder and 15 wt% of Fe-Co composite powder (70% Fe, 30% Co, D50 of 15 µm, flat sheet structure) were added sequentially and stirred at 100 rpm for 10 min to avoid powder breakage. Finally, an ethyl acetate solution containing 1 wt% vinylidene fluoride-hexafluoropropylene copolymer fluororubber (solid content 10 wt%) was added, and the stirring speed was adjusted to 150 rpm for 20 min. The mixture was then degassed in a 40 kHz, 200 W ultrasonic field for 5 min to eliminate air bubbles and obtain a uniform composite paste.
[0029] S4. Spray granulation and gradient drying: The composite paste was spray granulated using a two-fluid nozzle with an atomization pressure of 0.3 MPa, an inlet air temperature of 110℃, and an outlet air temperature of 75℃. After granulation, a gradient vacuum drying process was adopted, which was carried out in sequence at a gradient temperature of 25℃, 80℃, and 120℃ for a total drying time of 4 h, finally obtaining near-spherical composite powder particles with a particle size of 40~120 µm.
[0030] S5. Surface passivation treatment: The dried powder particles are placed in an ambient pressure and room temperature environment and subjected to plasma passivation treatment for 10 min using a 1 vol% O2 / Ar mixed atmosphere to form a dense and stable self-limiting oxide shell on the powder surface, ultimately obtaining a fast-burning, high-calorific-value heating powder.
[0031] Performance testing conditions and results: Combustion performance was tested using a 10 mL sealed ignition device with a charge of 1.0 g; electrical performance was tested by constant current discharge of a 1.0 g thermal battery. The measured loose charge density was 1.35 g·cm³. -3 Minimum total combustion time: 34 ms; heat of combustion: 33.1 kJ·g -1 Combustion residue: 4.2 wt%; maximum combustion pressure: 28.4 MPa; thermal battery activation time: 72 ms; discharge capacity: 125 mAh; peak operating temperature: 208℃.
[0032] Example 2 The preparation process in this embodiment is completely consistent with that in Example 1, except for the adjustment of the system composition ratio and alloy powder parameters: Al-Mg-B ternary alloy powder addition of 50 wt% (component ratio Al 60% / Mg 30% / B 10%), Fe-Co composite powder of 20 wt%, composite oxidant of 22 wt% (KClO4:CuO=3:1), carbon nanotube / graphene thermal conductive framework of 6 wt%, and fluororubber binder-pore-forming agent of 2 wt%. All other preparation process parameters and procedures remain consistent with those in Example 1.
[0033] Under standardized testing conditions, the bulk density of the heated powder in this embodiment is 1.28 g·cm³. -3 Minimum total combustion time 36 ms, calorific value of combustion 32.5 kJ·g -1 Combustion residue was 4.8 wt%, and the activation time of the assembled thermal cell was 78 ms.
[0034] Example 3 The preparation process in this embodiment is completely consistent with that in Example 1, except for adjustments to the system composition ratio and alloy powder parameters: 55 wt% Al-Mg-B ternary alloy powder (component ratio Al 70% / Mg 20% / B 10%), 18 wt% Fe-Co composite powder, 20 wt% composite oxidant (KClO4:CuO=5:1), 5 wt% carbon nanotube / graphene thermally conductive framework, and 2 wt% fluororubber binder-pore-forming agent. All other preparation process parameters and procedures remain consistent with Example 1.
[0035] Under standardized testing conditions, the bulk density of the heating powder in this embodiment is 1.40 g·cm³. -3The minimum total combustion time is 32 ms, and the heat of combustion is 33.8 kJ·g. -1 Combustion residue was 3.9 wt%, and the activation time of the assembled thermal cell was 68 ms.
[0036] Comparative Example 1 Traditional thermal battery heating powder was prepared according to the classic formulation and preparation method of Example 1 of authorized patent CN110890565B. A Fe-KClO4 basic system was used, combined with sodium salt additives and a heat storage layer structure. The heating powder was prepared through simple mechanical mixing and dry powder molding. All test conditions were completely consistent with those of the embodiments of this invention.
[0037] Performance test results: maximum combustion pressure 22.1 MPa, combustion time 52 ms, combustion residue 8.7 wt%; when equipped with a thermal battery of the same specifications, constant current 1 A discharge test, activation time 105 ms, discharge capacity 108 mAh.
[0038] Comparative Example 2 The preparation process was the same as in Example 1, except that traditional Al-Mg binary alloy powder was used instead of the Al-Mg-B ternary alloy powder of this invention, and the carbon nanotube / graphene thermally conductive framework and fluororubber pore-forming bonding system were omitted. The component ratio was: 60 wt% Al-Mg binary alloy powder, 20 wt% Fe-Co composite powder, 20 wt% composite oxidant, and 0 wt% addition of thermally conductive framework and fluororubber. The remaining preparation process and testing conditions were the same as in Example 1.
[0039] The tested comparative example of heated powder has a bulk density of 1.50 g·cm³. -3 Minimum total combustion time: 58 ms; Heat of combustion: 24.5 kJ·g -1 Combustion residue 12.5 wt%, assembly thermal cell activation time 130 ms.
[0040] Comparative Example 3 The preparation process was the same as in Example 1, except that the porous composite oxidant was replaced with a simple mechanical mixture of KClO4 and CuO powder, and the component ratio was adjusted as follows: Al-Mg-B ternary alloy powder 45 wt%, Fe-Co composite powder 15 wt%, mechanically mixed oxidant 30 wt%, thermally conductive framework 5 wt%, and fluororubber 5 wt%. The anti-solvent precipitation-freeze-drying pore-forming process and the powder plasma passivation treatment were omitted. The remaining test conditions were the same as in Example 1.
[0041] The tested comparative example of heated powder has a loose pack density of 1.20 g·cm³. -3 Minimum total combustion time 45 ms, calorific value of combustion 28.1 kJ·g -1 Combustion residue 7.5 wt%, assembly thermal cell activation time 110 ms.
[0042] Table 1 Key component parameters of Examples 2-3 and Comparative Examples 2-3
[0043] Table 2 Overall performance test results of each embodiment and comparative example
[0044] Comprehensive performance analysis As shown in the test data above, the heating powder prepared by this invention, through the synergistic combination of an Al-Mg-B ternary alloy high-energy fuel system, a porous composite oxidant, a carbon nanotube / graphene three-dimensional thermally conductive framework, and a fluororubber micro-explosion pore-forming structure, combined with plasma passivation modification and spray granulation refinement processes, exhibits significant advantages over the traditional Fe / KClO4 system (Comparative Example 1), the binary alloy non-thermally conductive system (Comparative Example 2), and the mechanically mixed oxidant system (Comparative Example 3). The heat of combustion of each embodiment of this invention can reach 32.5~33.8 kJ·g. -1 The combustion efficiency is significantly higher than that of other comparative studies; the total combustion time is only 32~36 ms, with a substantial increase in combustion rate; the combustion residue is controlled at 3.9~4.8 wt%, with a significant reduction in residue; and the activation time of the matching thermal battery is ≤78 ms, resulting in a faster start-up response. Simultaneously, the ternary boron alloy overcomes the passivation problem of the oxide film on the surface of traditional fuels, the three-dimensional thermal conductive network solves the problem of "external charring and internal combustion" in the powder, and the porous oxidant and pore-forming structure significantly improve combustion completeness, effectively solving the technical defects of existing heating powders such as low calorific value, slow combustion rate, excessive residue, and delayed battery activation.
Claims
1. A fast-burning, high-calorific-value heating powder, characterized in that, Includes the following components by mass percentage: a) 35%~55% Al-Mg-B ternary alloy powder; b) 15%~25% Fe-Co composite powder; c) 20%~30% of a composite oxidant, wherein the composite oxidant is a complex of KClO4 and CuO; d) 3%~8% thermally conductive framework, which is composed of carbon nanotubes and graphene sheets; e) 0.5%~2% of fluororubber-based adhesive-pore-forming agent; The loose density of the heating powder is 1.25~1.45 g·cm³. -3 The minimum total combustion time under 25℃ and 1 atm air conditions is ≤38 ms, and the kinetic heat of combustion is ≥32 kJ·g. -1 The mass fraction of combustion residue is ≤5 wt%.
2. The heating powder according to claim 1, characterized in that: The Al-Mg-B ternary alloy powder has the following mass percentages: Al 50%~70%, Mg 20%~35%, and B 5%~15%; the median particle size D50 of the alloy powder is 8~15 µm, and the maximum particle size is ≤45 µm.
3. The heating powder according to claim 1, characterized in that: In the Fe-Co composite powder, the mass percentages of Fe and Co are 60%~80% and 20%~40%, respectively; the median particle size D50 of the Fe-Co composite powder is 12~20 µm.
4. The heating powder according to claim 1, characterized in that: The composite oxidant is a porous particle obtained by anti-solvent precipitation-freeze-drying of KClO4 and CuO in a mass ratio of 3:1 to 5:1, with a D50 of 20 to 35 µm and a specific surface area ≥ 2.5 m². 2 ·g -1 In the thermally conductive framework, the mass ratio of carbon nanotubes to graphene sheets is 1:2 to 2:1; the volume resistivity of the thermally conductive framework is ≤1×10⁻⁶. -3 Ω·cm; the fluororubber is a vinylidene fluoride-hexafluoropropylene copolymer with a Mooney viscosity of (30~50) mu at ML(1+10)@120℃; the fluororubber-based binder-pore-forming agent decomposes at 250~350℃ to produce 0.3~0.8 mL·g -1 Combustible gas.
5. The heating powder according to claim 1, characterized in that: The surface of the Al-Mg-B ternary alloy powder has a self-limiting oxide shell with a thickness of 2~5 nm, which is formed by plasma passivation for 5~15 min at room temperature in an Ar mixed atmosphere containing 0.5~1 vol% O2.
6. The heating powder according to claim 1, characterized in that: The Fe-Co composite powder is a flat, sheet-like particle obtained by high-energy ball milling, with a sheet thickness of 0.5~2 µm, a sheet diameter of 10~30 µm, and an aspect ratio of 5~15; and / or, the composite oxidant particles have through-pores with a pore size of 50~200 nm and a pore volume of 0.15~0.25 cm³. 3 ·g -1 .
7. The heating powder according to claim 1, characterized in that: The thermally conductive skeleton is surface-modified with 3-aminopropyltriethoxysilane to achieve an interfacial shear strength ≥25 MPa with the fluororubber matrix.
8. A method for preparing the fast-burning, high-calorific-value heating powder according to any one of claims 1 to 7, characterized in that: Includes the following steps: S1. Alloy powder preparation: Al ingots, Mg ingots and B powder are induction melted in the target ratio and then atomized. The resulting powder is ball-milled to obtain Al-Mg-B ternary alloy powder with D50 of 8~15 µm. S2. Preparation of composite oxidant: KClO4 and CuO are dissolved in hot water in a certain proportion to form a saturated solution, which is then quickly poured into low-temperature ethanol for anti-solvent precipitation, and then freeze-dried to obtain a porous composite oxidant. S3, Triple Coupling Mixing: The thermally conductive framework is ultrasonically dispersed in an organic solvent to form a conductive paste. Then, a composite oxidant, Al-Mg-B ternary alloy powder, Fe-Co composite powder and fluororubber solution are added in sequence. Ultrasonic degassing is performed during stirring to obtain a uniform paste. S4. Spray granulation and drying: The paste is spray granulated and then subjected to gradient vacuum drying to obtain near-spherical particles; S5. Surface passivation treatment: The obtained particles are subjected to plasma treatment in an oxygen-containing inert atmosphere to obtain the fast-burning, high-calorific-value heating powder.
9. The preparation method according to claim 8, characterized in that: The ball milling described in step S1 is a differential step ball milling, with the following process parameters: n-hexane as the process control agent, ball-to-material ratio of 10:1, rotation speed of 350 rpm, 15 min of ball milling followed by a 5 min pause, and a total of 90 min of ball milling.
10. The preparation method according to claim 9, characterized in that: Step S3 specifically includes: ultrasonicating the thermally conductive framework in ethyl acetate for 10 min to form a conductive paste, then adding a composite oxidant and stirring at 200 rpm for 15 min; then adding Al-Mg-B ternary alloy powder and Fe-Co composite powder and mixing at 100 rpm for 10 min; finally adding an ethyl acetate solution of fluororubber, continuing to stir at 150 rpm for 20 min, and degassing in an ultrasonic field of 40 kHz and 200 W for 5 min; The parameters for spray granulation in step S4 are: a two-fluid nozzle, atomization pressure of 0.3 MPa, inlet air temperature of 110℃, and outlet air temperature of 75℃; the parameters for gradient vacuum drying are: vacuum drying at three temperature gradients of 25℃, 80℃, and 120℃ for a period of time each, with a total drying time of 4 h.
Citation Information
Patent Citations
A method for preparing a composite heating element for a thermal battery and its application
CN110890565B
Fast-burning high-calorific-value heating powder and preparation method thereof
CN119069732A